EVALUASI PENDIDIKAN NASIONAL ERA PANDEMI BERSANDAR PADA CHAOS THEORY - Mochamad Ichsan Nur; Ismail Marzuki (Universitas Muhammadiyah Tangerang, 2020)
Chaos theory is one scientific theory that has a more or less understanding: the theory that suggests about how chaotic that occurs both intentionally and unintentionally turns out to have a very big influence in the future. Simple can be understood between the system and the phenomena that occur are not linear, causing chaos. Pandemic it self is an appeal status issued by the World Health Organization (WHO) related to Covid-19, which is a big phenomenon that emerged in early 2019 in Wuhan, China. Entering the human health sector, resulting in death which is quite shocking the world statistically humanity. Until finally WHO issued a Pandemic status for all countries. This affects the national education system in which there is an evaluation of education. This paper tries to analyze the interaction of chaos theory / chaos theory with the evaluation of national education.